A formação do pedagogo na perspectiva da educação em saúde - Haboba, Lucia Aba Youssef [UNIFESP] (2017)
The following work aims to analyze the pedagogue’s formation by the perspective of health education. For the job outlining, it was decided for a Qualitative Research with a methodological triangulation. It is an exploratory descriptive study supported by documental analysis, focus group and semi-structured interviews. The analyzed documents refer to National Curricular Guidelines (DCN) for Pedagogy course, National Curricular Parameters (PCN) for Elementary School (Ensino Fundamental I), Elementary School’s National Curricular References (RCNEI), Political-Pedagogic Project (PPP), the menus and contents of São Paulo’s private Institution of Higher Education. The research population was composed by Pedagogy’s teachers and students. The data collection occurred in two moments - first with two teachers, when the interviews were recorded and transcribed in order to perform the data analysis by content analysis technic. In a second moment, the data collection occurred on the focus group, which was composed by 10 female students of Pedagogy who had reached at least the second year. The interviews were recorded, transcribed and also analyzed using the same technic. The study is in line with research ethical rules and has been authorized by the Research Ethics Committee of the Universidade Federal de São Paulo (CAAE: 52855316.8.0000.5505). By the documental analysis it was concluded that, in the PCNs and the RCNEIs, there is a curricular content that explores heavily some specific health areas such as nutrition and psychology over a generalist and social vision. This perspective is also identified in the curricular organization of the current course. It is important to highlight that the Pedagogy DCNs has, in the other hand, a more generalist approach. The data obtained by the interviews and the focus group has showed that the involved actors’ perception was in accordance with the pedagogue formation process, as the guiding cores were repeated in both contexts. The guiding core Teacher’s Formation highlighted the following aspects: The necessary usage of active methodologies during the formation process and appropriate language to each age group, so as the clearer definition of curricular contents related to health. The guiding core Health Education highlighted the presence of heath concepts as multifactorial, also the necessary stimulus since the elementary school in order to development of a health and self-knowledge promotion for self-care.